Minimally Invasive Right Infra-Axillary Approach for Mitral Valve Replacement: Our Initial Experience - Bhattarai, Anil; Khakural, Prabhat; Shrestha, Yuna (Journal of Institute of Medicine Nepal, 2024)
Introduction Minimally invasive approach for cardiac surgery is getting popular as compared to the traditional median sternotomy due to various benefits associated with the approach. Right vertical axillary approach for mitral valve replacement with peripheral cannulation was recently introduced in our center. We share our initial experience of the approach. Methods A descriptive study including eleven patients undergoing minimally invasive mitral valve replacement via right infra-axillary approach from June, 2024 to October, 2024 for rheumatic mitral valve disease was conducted. Data on patient demographics, clinical characteristics, echocardiographic findings, intra-operative variables and post-operative outcomes were evaluated. Statistical analysis was performed using Microsoft Excel 2016. Frequency, percentage, mean and standard deviation were calculated. Results Among 280 cardiac surgeries, 11 patients underwent minimally invasive mitral valve replacement in five months at our institute. The mean age of the patients was 47.63 ± 12.40 years (range 23- 62 years). Six patients were in 50-60 years age group. The majority of the patients (81.81%) were females. The main presenting symptoms were shortness of breath and palpitation. The mean Aortic cross clamp time was 81.36 ± 24.73 minutes and cardiopulmonary bypass time was 105.63 ± 32.23 minutes. There were no re-explorations and conversions to median sternotomy. There was no perioperative mortality. Conclusion Minimally invasive mitral valve replacement through right vertical infra-axillary approach is feasible in our setting and offers favorable post-operative outcome.